Low topographic positions enhance woody vegetation stability in the Ferlo (Senegalese Sahel). (April 2020) - Dendoncker, Morgane; Vincke, Caroline
Abstract: Woody vegetation provides multiple services to the pastoralists in the Sahel and since the drought of 1972–1984, concerns have been raised about its persistence. Some studies have observed a decline in tree density and specific richness while others have reported a greening at a larger scale. In this study, an extensive field inventory was carried out around two deep wells in the Ferlo (Senegal). The influence of topography and proximity of deep wells on woody vegetation density, diversity and regeneration was studied. An analysis of the size class distribution was carried out to gain insight into the population dynamics of some species. This study highlights the key role of low topographic positions in favouring woody vegetation establishment with a higher species richness and a greater density. The remoteness of deep wells seems to have no effect on these variables. The instability of several tree species populations was evident from the size class analysis. As large trees play an important role in hosting regeneration, the persistence of the current woody vegetation is threatened. Given the positive impact of depressions on woody vegetation, further research should focus on these topographic features and their role as central pieces in a potential management plan. Highlights: Topography highly determines the diversity and the structure of woody vegetation. Density of adults and seedlings are higher inside depressions than on tops. Depressions host a higher specific richness than the tops. Only three species over 24 present a stable population structure.